Pengenalan swamedikasi dengan metode CBIA pada kader Fatayat Nahdatul Ulama Kota Mataram - Muhammad Farid Rizki; Fatya Kamila Putri; Kurnia Solehah; Lalu Husnul Hidayat; Khairun Nisa; Raisya Hasina; Iman Surya Pratama; Siti Rahmatul Aini (Universitas Mataram, 2023)
The ability to promote health, prevent disease, maintain health, and deal with illness and disability with or without the assistance of a healthcare provider is known as self-care. Irrational self-medication can have a variety of harmful effects. The government has taken action to reduce the unjustified use of medicine for self-medication. However, The distribution of this program, particularly in Islamic residential schools and religious institutions, needs to be more equitable. As an Islamic youth organization under the Nahdlatul Ulama, Fatayat is expected to assist in helping the community use medicine carefully. The program was held on November 13, 2022, at Musholla Umi Wartiah Sekarbela. Lectures, facilitated discussions, and guidance with worksheet completion made the learning method. Classical methods are used for material provision, and the team provides group coaching. The attendees were engaged in each session, following along closely and actively participating in the discussion. This program's key messages are that multiple drugs can have the same indication/efficacy and that different drug names can have the same active component. This activity aims to make participants aware of how critical it is to check the drug packaging to verify the active components and indications